NITROUS OXIDE/OXYGEN CONSCIOUS SEDATION IN ASA CLASS II DENTAL PATIENTS - PART 1 - Liviu Ioan Tuturici; Octavian Dincă; Cristina Pădurariu; Tiberiu Niță; Cristian Vlădan; Alexandru Bucur (Romanian Society of Oral Rehabilitation, 2022)
Aim of the study The use of nitrous oxide/oxygen conscious sedation in American Society of Anesthesiologists (ASA) II dental patients has been regarded as controversial. The aim of this study was to investigate cardiovascular effects of nitrous oxide-oxygen mixture conscious sedation in ASA II patients undergoing tooth extraction. Material and methods The purpose of this study was to determine differences in heart rate (HR) and blood pressure (BP), comparing nitrous oxide/oxygen with no sedation in a sample of ASA II patients. Physiologic parameters measured were heart and respiratory rate, systolic and diastolic blood pressure and oxygen saturation. Categorical data are summarized as percentages, and differences between groups were tested using Stata/IC 16 software (StataCorp). Ethical approval from the local institutional ethics comitee was obtained for this study. Results Results did not indicated differences for any physiologic parameters, including heart rate and diastolic blood pressure. Significant differences across procedures were found for systolic blood pressure. Conclusions Although the effects of nitrous oxide/oxygen may not be statistically significant, generally it produces an attenuation in physiological responses as measured under the conditions of this study in ASA II patients.